2018
DOI: 10.1016/j.euromechflu.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effect of non-Newtonian behavior of blood flow in the Fontan circulation

Abstract: The Fontan procedure for univentricular heart defects creates a unique circulation where all pulmonary blood flow is passively supplied directly from systemic veins. Computational simulations, aimed at optimizing the surgery, have assumed blood to be a Newtonian fluid without evaluating the potential error introduced by this assumption. We compared flow behavior between a non-Newtonian blood analog (0.04% xanthan gum) and a control Newtonian fluid (45% glycerol) in a simplified model of the Fontan circulation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…In these settings, wall shear stress and areas of increased thrombotic potential may be characterized inaccurately when using a Newtonian fluid assumption. Expanding upon our prior clinical and experimental observations (10,11), we similarly demonstrate in the present study that non-Newtonian behavior affects power loss, pulmonary flow distribution, caval flow mixing, and shear stress in patient-derived synthetic models of the low-shear Fontan circulation. Since each of these factors can affect the long-term sequelae of the Fontan circulation, accurate measurements that incorporate non-Newtonian behavior (i.e., using 4D flow MRI in conjunction with computational fluid dynamic modeling) are necessary to properly risk stratify these patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In these settings, wall shear stress and areas of increased thrombotic potential may be characterized inaccurately when using a Newtonian fluid assumption. Expanding upon our prior clinical and experimental observations (10,11), we similarly demonstrate in the present study that non-Newtonian behavior affects power loss, pulmonary flow distribution, caval flow mixing, and shear stress in patient-derived synthetic models of the low-shear Fontan circulation. Since each of these factors can affect the long-term sequelae of the Fontan circulation, accurate measurements that incorporate non-Newtonian behavior (i.e., using 4D flow MRI in conjunction with computational fluid dynamic modeling) are necessary to properly risk stratify these patients.…”
Section: Discussionsupporting
confidence: 80%
“…We previously demonstrated that non-Newtonian behavior negatively impacts pulmonary blood flow in children with Glenn and Fontan circulations (11) and alters power loss, flows, and wall shear stress in a simplified synthetic model of the Fontan circulation (10). Expanding upon these observations, the goal of this study was to use four-dimensional (4D) flow magnetic resonance imaging (MRI) to evaluate how realistic non-Newtonian viscosity affects flow in patient-specific experimental models of the Fontan circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement uncertainties regarding the pressure transducers and owmeters were approximately 2%. A non-Newtonian single-phase blood analog that has been reported to closely match the blood viscosity of Fontan patients [51,52] was prepared and used as the working uid.…”
Section: Pulsatile In Vitro Mock Circulatory Loopmentioning
confidence: 99%
“…However, recent studies on simplified dilation geometries, such as is seen in the sinus, reveals the significant differences in WSS-related parameters seen with even small changes in the viscoelastic and shear-thinning behavior of blood ( Bilgi and Atalik, 2019 , 2020 ). Furthermore, experiments on Fontan hemodynamics highlight that neglecting non-Newtonian behavior like shear-thinning can produce significant errors and misinterpretation of the hemodynamics ( Cheng et al, 2018a , b , 2019 ; Wei H. et al, 2020 ; Wei Z. et al, 2020 ). These studies demonstrate the important role of shear-thinning relevant to specific clinical problems such as Fontan flows and aneurysms.…”
Section: The Unique Flow and Shear Stress Characteristics Of The Carotid Sinusmentioning
confidence: 99%